2014
DOI: 10.1021/cg401897n
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tunable Oligophosphonates on Barium Sulfate Crystallization

Abstract: Calixarenes can be used as well-defined scaffolds for investigating structure-activity relationships of additives and their impact on crystallization. In this work we present the crystal growth modification of barium sulfate by p-phosphonic acid calix[n]arene, which vary in size, n = 4, 5, 6 and 8, and thus vary in the size of the internal cavity for the same functionality in the upper rim. The tetrameric, hexameric and octameric macrocycles induce nanoparticle formation with clear superstructure. In the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Calixarenes bearing phosphonic acid groups have been shown to induce the mesocrystal formation of barium sulfate, despite being relatively low-molecular-weight additives. These calixarenes are a synthesis in three steps from the parent calixarene by bromination of the aromatic rings, substitution with a phosphonodiester, and reaction of this with bromotrimethylsilane to give the calixarene tetraphosphonic acid, as shown in Figure . …”
Section: Miscellaneous Phosphonate Sismentioning
confidence: 99%
“…Calixarenes bearing phosphonic acid groups have been shown to induce the mesocrystal formation of barium sulfate, despite being relatively low-molecular-weight additives. These calixarenes are a synthesis in three steps from the parent calixarene by bromination of the aromatic rings, substitution with a phosphonodiester, and reaction of this with bromotrimethylsilane to give the calixarene tetraphosphonic acid, as shown in Figure . …”
Section: Miscellaneous Phosphonate Sismentioning
confidence: 99%
“…7 To improve understanding of additive-crystal interactions, we, and others, have studied the impact of sequences of additives with systematically changed structures. 4,[8][9][10][11][12] Given that subtle changes in additive structure can have a large impact on crystal growth, we became interested in the idea of using a "switchable" additive, inspired by the remarkable range of stimuli-responsive materials that have been developed. 13 These materials have applications in light powered engines, 14 photo-responsive liquid crystals, 15 polymers, 16 molecular electronics, 17 holographic optical data storage, 18 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There has been much work conducted in the area of mesocrystals and their formation in the presence of polymeric species. [8][9][10][11] We have, in the past, shown that small molecules can stabilise barium sulfate and that this is most likely due to self-assembly of the organic molecule [12][13][14] resulting in the steric stabilisation required. Formation of meso-crystals is also possible by charge stabilisation of nanoparticles 15,16 rather than steric stabilisation since the general mechanism relies on any form of stabilization of the initial nanoparticle before formation of the mesocrystal and/or fusion to an iso-oriented crystal.…”
Section: Introductionmentioning
confidence: 99%